(3JPcQI GdabgGAs - (3GdMSf (B- (3hjbGd(B: (3GdMSjf (B- (3Hf jhSa GHf Ydj Hf GdeWgQ GdMdj, LeGd GdOjf,J (B726 (3g` s ((3ZjGK GdOjf Hf YHO GdSejY Hf ajGV GdCSOi s)
(3ChdgG (B:s
(3eHJOF ef Chd GdcJGH s
(3BNQgG (B:s
(3BNQ cJGH GdUdGI s
(3GdfSNI HgG MhGTs
(3dNU ajg aJGhi GdYdeGA hPcQ bhGYO GdabgGA Ydi CMb GdWQGFb hChKbgG hgj WQjbI GdEeGejIs
(3efbhd Yf fSNI GdeUfas
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3abg GdePGgH GdCNQis